Correlation and path coefficients analyses in Basmati rice - Ratna, M; Begum, S; Husna, A; Dey, SR; Hossain, MS (Bangladesh Journal of Agricultural Research, 2015)
Correlation and path coefficients analyses among fourteen morphological characters were studied in six advanced lines of Basmati rice and one commercial check namely BRRI Dhan 29. In general, genotypic correlation coefficients were higher than the corresponding phenotypic correlation coefficients suggesting that the environmental influence reduces the relationship between yield and yield contributing characters of rice. Correlation coefficient analysis showed significant positive correlation between plant height and panicle length at genotypic level. Number of filled spikelets/panicle showed significant positive correlation with yield at both genotypic and phenotypic levels but significant negative correlation was observed between plant height and yield. Number of effective tillers/plant had negative significant correlation with panicle length and with number of unfilled spikelets/panicle at genotypic level. Number of ineffective tillers/plant had significant negative correlation with 1000-seed weight at both genotypic and phenotypic levels. Path coefficient analysis revealed highest positive direct effect of number of filled spikelets/panicle on grain yield but plant height and number of unfilled spikelets/panicle had negative direct effect on grain. Bangladesh J. Agril. Res. 40(1): 153-161, March 2015